Motivation factors and barriers for continuing higher education among diploma-holding nurses: a qualitative study - Anthonysamy, Kaslen; Wan Mamat, Wan Hasliza (Panyapiwat Institute of Management (PIM), 2024)
Background: Continuing higher education is essential for nurses to adapt to the evolving landscape of healthcare. Higher education is the next level in the academic ladder for nurses seeking a bachelor’s or postgraduate degree, such as a master’s or Ph.D. Nurses pursuing higher education are known to improve educational, research, administrative, and patient outcomes. Furthermore, the need for nurses to pursue further education in order to advance their profession is becoming increasingly pressing due to the rapid advancements in health care and therapies. Aim: To explore the motivational factors and barriers for continuing higher education among diploma holding nurses in Malaysia. Method: A qualitative study was conducted among 9 diploma-holding nurses in Malaysia. Semi-structured interviewed were used to collect data from August to October 2023. All interviews were recorded, translated, and transcribed. Thematic analysis was applied to the transcriptions for a comprehensive examination of the gathered data. Result: Six themes identified related to motivating factors; 1) significant others, 2) self-motivation 3) reputation of the nursing profession, 4) career improvement, 5) sponsorship, and 6) availability of course while five themes associated with barriers; 1) limited opportunity in the nursing system, 2) age and experiences, 3) financial constraint, 4) family responsibility, and 5) limited access to educational resource. Conclusion: Nurses are highly motivated to pursue higher education at least to degree level for many reasons but they face some barriers that restrict them from continuing higher education. Therefore, it is important as health treatments and care evolve, the motivation to advance the nursing profession through higher education becomes increasingly important for nurses.